DAMPAK PERTUMBUHAN PENDUDUK TERHADAP INFRASTRUKTUR DI KOTA SEMARANG - Arga Satria Arsandi; Dimas Wahyu R (Jurnal Riptek, 2018)
Semarang city is the capital of Central Java Province where population growth is increasing rapidly every year. As the capital province, the city is required to be able to  ensure the needs of the population. It is encouraging the urban population and the regional division in the city. Infrastructure plays an important role in supporting the process where it is governed by the policies. The purpose of this study is identifying the development of infrastructure in Semarang, analyzed population growth, economic areas, road networks and policies that affect the development of infrastructure in Semarang and evaluate policies that affect the development of infrastructure in Semarang. The method used in this study is the analysis of descriptive and a correlation. Object in the study is identifying population growth and infrastructure development. The primary that is needed in the form of a picture of the infrastructure building and transportation in the city, as for data source has obtained from research ever done before, these data are issued by relevant agencies. The collection of data used is the camera to take pictures and videos that serves to support the data. The conclusion of this research is a factor of the population density is the most influential to the effects of the development of infrastructure in Semarang. The impact caused by population growth is rising fast population growth in areas of the city where it affects the development of infrastructure in the area. For the infrastructure policy, there are still some who need to be updated, because it is still not as if implemented in the field. And for that, in this research given recommendations for the policy infrastructure.